(untitled) (Indian Journal of Forensic Medicine & Toxicology, 2020)
This study was performed to assess knowledge, attitudes, and practices towards breastfeeding and identify factors impacting this practice among mothers. A descriptive case-series study was carried out among 220 mothers who had a child less than 2 years, in Ibrahim Pasha Health Center in Sulaimani city, between the 9th of August 2018 and 20th of November 2018. The convenience sampling method was used to select the subjects. Mean age of the mothers was 29.37 years. More than half (56.8%) of the mothers were encouraged for breastfeeding, the main encouragement factors were husbands, medical staff, and other families (45%, 22%, and 15% respectively). More than one third (37.7%) of the mothers ceased breastfeeding, the main motives were producing insufficient milk, child refusal and child’s disease (31%, 25%, and 17% respectively). The association between mode of delivery and types of feeding was statistically significant (P=0.028); exclusive breastfeeding was high in the normal delivery group. Overall, the mothers had a good knowledge and a positive attitude toward breastfeeding. Only 30.5% of the mothers started breastfeeding within the first hour after labour. An extreme number (95%) of the mothers fed colostrum to their baby. Merely 30.5% of the participants fed their babies exclusively.